The Prior of the Knights Hospitaller in late medieval England - Phillips, Simon (Simon David) (Boydell Press, 2009)
The Prior of the Knights Hospitaller played a major role not only within the Order, but also in the wider arena of English - and indeed European - politics. This role, and its changes between 1272 and 1540, are the focus of this new book, which draws exte.